Analisis Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah (Bos) Di UPTD SD NEGERI 071076 Ombolata - Mery Ratnajuwita Dohona; Nanny A. Buulolo; Serniati Zebua; Martha S.D. Mendrofa (Visi Sosial Humaniora, 2024)
Education is one of the fundamental things related to the quality of a nation's human resources. In the 1945 Constitution of the Republic of Indonesia, Article 31 paragraph (1) mandates that every citizen has the right to education. The School Operational Assistance Program (BOS) is public funds obtained by education units to ease the burden on the Indonesian people. The aim of this research is to analyze the effectiveness of managing School Operational Assistance (BOS) funds. The method used in this research is quantitative methods, data collection techniques using observation, interviews and documentation. The research results show that the management of BOS funds at UPTD SD Negeri 071076 Ombolata during 2021-2023 is effective because the School Budget Activity Plan (RKAS) and budget realization are in accordance with what was previously budgeted so that it is said to be effective.